Pedagogical Content Knowledge-Guided Lesson Study: Effects on Teacher Competence and Students' Achievement in Chemistry. (29th November 2016) - Lucenario, John Lou S.; Yangco, Rosanelia T.; Punzalan, Amelia E.; Espinosa, Allen A.
Abstract : This study aimed to investigate the effectiveness of Pedagogical Content Knowledge-Guided Lesson Study (PCKLS) as an intervention to develop PCK competencies among teachers and consequently enhance student achievement in terms of conceptual understanding and problem-solving skills. Using quasi-experimental design, teacher competencies and student achievement in the PCKLS group and the conventional group were compared. In the PCKLS group, the intervention involved planning the lesson by the research team, teaching the planned lesson while PCK observations were made by the researcher and another teacher from the group, including a feedback meeting, implementing the improvements in the reteach stage of the lesson study cycle by another teacher from the research team, and, finally, revising lesson plans based on the consolidated suggestions for improvement. Analyses of data showed that there was a significant difference in the science teacher competencies of the PCKLS group teacher respondents compared to those of the conventional group. Also, student respondents showed a significant increase on mean scores in terms of conceptual understanding and problem-solving skills. Therefore, it was concluded that PCKLS was an effective method to develop the teachers' PCK competencies and student achievement in terms of conceptual understanding and problem solving. This study recommends that this intervention be used across chemistry topics and in other science classes such as Biology, Earth and Environmental Science, Physics, and Mathematics.